Neurocognitive outcomes following fetal exposure to chemotherapy for gestational breast cancer: A Canadian multi-center cohort study. (August 2021) - Maxwell, Cynthia; Alavifard, Sepand; Warner, Ellen; Barrera, Maru; Brezden-Masley, Christine; Colapinto, Nicolas; Kassirian, Shima; Madarnas, Yolanda; Srikala, Sridhar; Tozer, Richard; Yu, Joanne; Nulman, Irena
Abstract: Background: Limited knowledge exists on outcomes of children exposed prenatally to chemotherapy for breast cancer (BC). The purpose of this study was to compare long-term neurocognitive, behavioral, developmental, growth, and health outcomes of children exposed in-utero to chemotherapy for BC. Methods: This is a multi-center matched cross-sectional cohort study involving seven cancer centers across the region of Southern Ontario (Canada), and the Hospital for Sick Children (Toronto, Ontario). Using standardized psychological and behavioral tests, we compared cognitive and behavioral outcomes in children exposed to chemotherapy during pregnancy for BC to age-matched pairs exposed to known non-teratogens. Results: We recruited 17 parent-child pairs and their matched controls. There were more preterm deliveries in the chemotherapy-exposed group compared to controls (p < 0.05). Full Scale IQ of children in the chemotherapy group was significantly confounded by maternal IQ and prematurity. Exposed children born at term were not different in cognitive outcomes. Children from both groups were similar in their developmental milestones, pediatric anthropometric measurements and health problems. There were no cases of autoimmune cytopenia. Conclusions: This is the first Canadian prospective comparative study designed to assess pediatric cognition following prenatal exposure to chemotherapy for BC. Chemotherapy was not found to be neurotoxic in this cohort and did not affect pediatric health. The decision to plan a preterm birth for initiating or continuing chemotherapy treatment must be taken into consideration in context of pediatric implications. While these results may assist in such decision making, replication with a larger sample is needed for more conclusive findings. Highlights: Limited knowledge exists on outcomes of children exposed prenatally to chemotherapy for breast cancer (BC). We compared cognitive and behavioral outcomes in children exposed to chemotherapy during pregnancy for BC to controls. FSIQ of children in the chemotherapy group was significantly confounded by prematurity. Chemotherapy was not found to be neurotoxic and did not affect pediatric health. Pediatric implications of planned preterm birth for further treatment should be considered.